Reading a book can change your mind, but only some changes last for a year: food attitude changes in readers of The Omnivore's Dilemma - Hormes, Julia M.; Rozin, Paul; Green, Melanie C.; Fincher, Katrina (Frontiers in Psychology, 2013)
Attitude change is a critical component of health behavior change, but has rarely been studied longitudinally following extensive exposures to persuasive materials such as full-length movies, books, or plays. We examined changes in attitudes related to food production and consumption in college students who had read Michael Pollan's book The Omnivore's Dilemma as part of a University-wide reading project. Composite attitudes towards organic foods, local produce, meat, and the quality of the American food supply, as well as opposition to government subsidies, distrust in corporations, and commitment to the environmental movement were significantly and substantially impacted, in comparison to students who had not read the book. Much of the attitude change disappeared after one year; however, over the course of twelve months self-reported opposition to government subsidies and belief that the quality of the food supply is declining remained elevated in readers of the book, compared to non-readers. Findings have implications for our understanding of the nature of changes in attitudes to food and eating in response to extensive exposure to coherent and engaging messages targeting health behaviors.